Effects of a new parallel primary healthcare centre and on-campus training programme on history taking, physical examination skills and medical students' preparedness: a prospective comparative study in Taiwan. Issue 9 (25th September 2017) - Yang, Ying-Ying; Wang, Shuu-Jiun; Yang, Ling-Yu; Lirng, Jiing-Feng; Huang, Chia-Chang; Liang, Jen-Feng; Lee, Fa-Yauh; Hwang, Shinn-Jang; Huang, Chin-Chou; Kirby, Ralph
Abstract : Objectives: The primary healthcarecentre (PHCC) is the first place that medical students experience patient contact. Usually, medical students are frustrated by a lack of proper skills training for on-campus history taking (HT), physical examination (PE) and self-directed learning (SDL) to prepare for their PHCC and inhospital patient contact. For pre-clerks, this study aims to compare the effectiveness of PHCC training and PHCC training in combination with on-campus HT and PE training modules (PHCC+on-campus) on their clerkship preparedness. Design: This comparative study utilised prospective, consecutive, end of pre-clerkship group objective structured clinical examination (GOSCE), beginning of clerkship OSCE and self-administered Preparation for Hospital Practice Questionnaire (PHPQ). Setting/participants: 128 pre-clinical clerk volunteers (64 each year) receiving PHCC training (7 week PHCCtraining in addition to 7 week assignment based group learning, academic year 2014, controls) and PHCC training in combination with on-campus module training (academic year 2015, 7 week PHCCtraining in addition to 7 week on-campus sessions) were sequentially assessed before the module (week 1), at the end of the module (week 14) and at the beginning of clerkship (week 25). Results: For overall HT and PE skills, both PHCC and PHCC+on-campus module trained pre-clerks performed better on OSCE than GOSCE. Additionally, the improvement was accompanied by higher self-reported PHPQ scores in 'confidence/coping' and 'SDL' domains. At the end of the pre-clerkship and the beginning of the clerkship stages, the degree of improvement in preparedness in 'confidence/coping' and 'SDL' domains was higher for those in the PHCC+on-campus group than for those in the PHCC group. Among the PHCC+on-campus module participants, a positive association was observed between high mean PHPQ-SDL scores and high OSCE scores. Conclusions: Our study suggests that the PHCC+on-campus module, which is paired faculty led and pre-trained dyad student assisted, is effective in developing a preclinical clerk's HT and PE skills and intensifying SDL/patient management abilities to prepare for hospital practice in clerkship.